Novel thermoelectric materials: free-standing poly(ε-caprolactone)/poly(m-anthranilic acid)/Fe2O3, Fe3O4 nanofibers - Huner, Azra (SPRINGER INT PUBL AG, 2025)
Owing to global warming and the shortage of fossil fuel reserves, there has been a search for sustainable and cleaner energy sources. Thermoelectric (TE) generators, which are environmentally friendly alternatives using the Seebeck effect, can generate electricity with some of the waste heat and contribute to slowing the rate of global warming. It can be said that thermoelectric polymer materials have become more attractive than inorganic thermoelectric materials due to their high mechanical elasticity, non-toxicity, low cost, easy processability, and poor thermal conductivity. However, since the thermoelectric properties alone are not sufficient, the thermoelectric properties can be increased by adding conductive polymers, organic, inorganic, or polymeric nanoparticles. In this study, free-standing and flexible nanofiber composites were obtained with poly(epsilon-caprolactone) (PCL), poly(m-anthranilic acid) (PANA), Fe2O3, and Fe3O4 by the electrospinning method. The TE properties of the obtained nanofiber were investigated. The highest Seebeck coefficient and thermoelectric power factor were obtained from PCL/PANA/Fe3O4 nanofiber composite as 49 mu V/K and 0.13 mu W/mK2, respectively. Nanofibers were characterized by XRD and FTIR, and their surface morphology was examined by SEM.
Keywords: Nanofiber; Flexible thermoelectric materials; Poly(m-anthranilic acid); FILMS; ACID; POLYANILINE; SCAFFOLD; Chemistry